Oxidative inactivation of lactonase activity of purified human paraoxonase 1 (PON1) - Nguyen, Su Duy; Hung, Nguyen Dang; Cheon-Ho, Park; Ree, Kim Mee; Dai-Eun, Sok (Biochimica et biophysica acta, 2009)
Paraoxonase1 (PON1), one of HDL-associated antioxidant proteins, is known to lose its activity in vivo systems under oxidative stress. Here, we examined the effect of various oxidants on lactonase activity of PON1, and tried to protect the lactonase activity from oxidative inactivation. Among the oxidative systems tested, the ascorbate/Cu 2+ system was the most potent in inactivating the lactonase activity of purified PON1; in contrast to a limited role of Fe 2+, Cu 2+ (0.05–1.0 µM) remarkably enhanced the inactivation of PON1 in the presence of ascorbate (0.02–0.1 mM). Moreover, Cu 2+ alone inhibited the lactonase activity at concentrations as low as 1 µM. The ascorbate/Cu 2+-mediated inactivation of PON1 lactonase activity was prevented by catalase, but not general hydroxyl radical scavengers, suggesting the implication of Cu 2+-bound hydroxyl radicals in the oxidative inactivation. Compared to arylesterase activity, lactonase activity appears to be more sensitive to Cu 2+-catalyzed oxidation. Separately, ascorbate/Cu 2+-mediated inactivation of lactonase activity was prevented by oleic acid as well as phoshatidylcholine. Taken together, our data demonstrate that Cu 2+-catalyzed oxidation may be a primary factor to cause the decrease of PON1 lactonase activity under oxidative stress and that lactonase activity of PON1 is most susceptible to ascorbate/Cu 2+ among PON1 activities. In addition, we have showed that radical-induced inactivation of lactonase activity is prevented by some lipids.